Diaphragmatic Liver Herniation after Radiofrequency Ablation of a Secondary Liver Tumor - Hoskovec, David; Hořejš, Josef; Krška, Zdeněk; Argalácsová, Soňa; Klobušický, Pavol (Diagnostics (Basel, Switzerland), 2023)
Radiofrequency thermal ablation (RFA) is widely used and has been accepted for the treatment of unresectable tumors. The leading technique that is used is percutaneous RFA under CT or US guidance. Multicenter surveys report acceptable morbidity and mortality rates for RFA. The mortality rate ranges from 0.1% to 0.5%, the major complication rate ranges from 2% to 3%. Diaphragmatic injury is a rare complication and it is described after RFA of subdiaphragmatic tumors. Most of them are without clinical importance. There are some case reports about diaphragmatic herniation of the intestine into the pleural cavity. We present a case of diaphragmatic perforation resulting in the herniation of the liver into the pleural cavity. A thoracotomy was performed, the liver was lowered back into the peritoneal cavity and the perforation was closed with mesh.
Keywords: RFA; cancer; radiofrequency ablation; complication; diaphragm hernia